A novel real-time PCR assay for quantitative detection of Campylobacter fetus based on ribosomal sequences - Iraola, Gregorio (2016)
Background: Campylobacter fetus is a pathogen of major concern for animal and human health. The species shows a great intraspecific variation, with three subspecies: C. fetus subsp. fetus, C. fetus subsp. venerealis, and C. fetus subsp. testudinum. Campylobacter fetus fetus affects a broad range of hosts and induces abortion in sheep and cows. Campylobacter fetus venerealis is restricted to cattle and causes the endemic disease bovine genital campylobacteriosis, which triggers reproductive problems and is responsible for major economic losses. Campylobacter fetus testudinum has been proposed recently based on genetically divergent strains isolated from reptiles and humans. Both C. fetus fetus and C. fetus testudinum are opportunistic pathogens for immune-compromised humans. Biochemical tests remain as the gold standard for identifying C. fetus but the fastidious growing requirements and the lack of reliability and reproducibility of some biochemical tests motivated the development of molecular diagnostic tools. These methods have been successfully tested on bovine isolates but fail to detect some genetically divergent strains isolated from other hosts. The aim of the present study was to develop a highly specific molecular assay to identify and quantify C. fetus strains. Results: We developed a highly sensitive real-time PCR assay that targets a unique region of the 16S rRNA gene. This assay successfully detected all C. fetus strains, including those that were negative for the cstA gene-based assay used as a standard for molecular C. fetus identification. The assay showed high specificity and absence of cross-reactivity with other bacterial species. The analytical testing of the assay was determined using a standard curve. The assay demonstrated a wide dynamic range between 102 and 107 genome copies per reaction, and a good reproducibility with small intra- and inter-assay variability. Conclusions: The possibility to characterize samples in a rapid, sensitive and reproducible way makes this assay a good option to establish a new standard in molecular identification and quantification of C. fetus species.